High Human Immunodeficiency Virus (HIV) Viral Load and Coinfection with Viral Hepatitis Are Associated with Liver Enzyme Abnormalities among HIV Seropositive Patients on Antiretroviral Therapy in the Lake Victoria Zone, Tanzania - Shabani Iddi; Caroline A. Minja; Vitus Silago; Asteria Benjamin; Jastine Mpesha; Shimba Henerico; Benson R. Kidenya; Stephen E. Mshana; Mariam M. Mirambo (AIDS Research and Treatment)
Background. Liver enzymes abnormalities have been found to be common among patients on antiretroviral treatment (ART). Apart from the effects of ART on these changes, other factors that can potentially contribute to the abnormal levels of these enzymes have been found to vary in different geographical locations. This study investigated factors associated with liver enzymes abnormalities among human immunodeficiency virus (HIV) infected individuals on ART from the Lake Victoria zone, Tanzania. Methods. A cross-sectional study involving a total of 230 sera from HIV seropositive patients from different regions of the Lake Victoria zone was carried out in July 2017. All samples with required variables/parameters such as age, sex, ART regimen, and residence were serially included in the study. Hepatitis B virus (HBV) and Hepatitis C virus (HCV) detection and liver enzymes assays (alanine transaminase (ALAT) and aspartate transaminase (ASAT)) were assessed following the standard procedures. Data were analyzed by using STATA version 13. Results. The median age of the study participants was 38 (interquartile range [IQR]:30-48) years. The overall prevalence of abnormal liver enzymes was 43.04% (99/230, 95% CI: 36.6-49.3). A total of 26.09% (60/230) had elevated ASAT while 23.9% (55/230) patients had elevated ALAT levels. ASAT levels were significantly high among patients with high HIV viral load (P= 0.002) while ALAT levels were significantly high among those coinfected with hepatitis C virus (P=0.017) and hepatitis B virus (P<0.001). Conclusion. A significant proportion of HIV seropositive individuals on ART have abnormal levels of liver enzymes, which is significantly associated with high HIV viral load and viral hepatitis. This calls for the need to emphasize screening of viral hepatitis and provision of appropriate management among HIV seropositive individuals in this setting.